2016
DOI: 10.1042/bcj20160417
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay of prion-infected blood plasma in PrP transgenic Drosophila

Abstract: In pursuit of a tractable bioassay to assess blood prion infectivity, we have generated prion protein (PrP) transgenic Drosophila, which show a neurotoxic phenotype in adulthood after exposure to exogenous prions at the larval stage. Here, we determined the sensitivity of ovine PrP transgenic Drosophila to ovine prion infectivity by exposure of these flies to a dilution series of scrapie-infected sheep brain homogenate. Ovine PrP transgenic Drosophila showed a significant neurotoxic response to dilutions of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…However, recent studies suggest that these models hold a potential for studying, among other aspects, prion neurotoxicity [178], infectivity [177], and testing anti-prion compounds of sporadic and inherited prion disease [56]. …”
Section: Animal Models Of Prion Disease: From Monkeys To Fliesmentioning
confidence: 99%
“…However, recent studies suggest that these models hold a potential for studying, among other aspects, prion neurotoxicity [178], infectivity [177], and testing anti-prion compounds of sporadic and inherited prion disease [56]. …”
Section: Animal Models Of Prion Disease: From Monkeys To Fliesmentioning
confidence: 99%
“…Furthermore, Drosophila transgenic for hamster PrP variants generally showed a more severe neurotoxic phenotype than flies transgenic for mo3F4 FFI or mo3F4 CJD PrP. The neurotoxicity we observed in mutant PrP transgenic Drosophila is similar to that seen in ovine PrP transgenic Drosophila exposed to sheep scrapie prions [ 48 51 ]. We reasoned that the phenotype seen in mutant PrP transgenic Drosophila was associated with spontaneous prion formation since these flies were not exposed to a source of exogenous prion infectivity.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, Drosophila have several important positive experimental advantages including a short lifespan, simple genetics and a well-characterised genome that is amenable to transgenesis [ 45 – 47 ]. We have demonstrated that transmissible mammalian prion disease can be modelled in the fly [ 48 51 ]. Our studies have shown that PrP transgenic Drosophila develop a neurotoxic phenotype after exposure to exogenous prions that is associated with accumulation of PrP Sc and is transmissible to PrP transgenic hosts, including mice, two crucial hallmarks of bona fide mammalian prion diseases [ 48 51 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, apart from the development of new PrP Sc detection methods for diagnosis, PMCA has permitted to detect PrP Sc in extracellular vesicles from plasma of vCJD infected mice [244], which was later confirmed by IHC [245]. Although other methods have been proposed (e.g., rapid tests based on ELISA [18,246], cellular assays using prion susceptible cells [247], or bioassay in Drosophila [248]), the worse specificity and sensitivity and difficulties associated to cell culture or fly models for standardization purposes have limited their use. Nonetheless, several laboratories and companies have developed their own methods for screening of vCJD prions in blood based on distinct procedures.…”
Section: Prp Sc In Blood According To New Detection Techniquesmentioning
confidence: 99%